Natural Birth - Ekachai Kovavisarach; Tanit Habananand (The Royal Thai College of Obstetricians and Gynaecologists, 2012)
Nowadays, increasing numbers of people prefer to spend their lives close to Nature. Many natural products and ways of living have become popular around the world, including in Thailand. Natural birth, or active birth or mother friendly birth practice, as it is sometimes known, is the practice of birth care which encourages a mother to use her innate birthing instinct while receiving skilled, supportive care from qualified health professionals. An interesting and important question for health professionals caring for women in labor is 'How do we view birth?' Is birth seen as a physiological or pathological process? Or for that matter, are the changes of pregnancy physiological or pathological? Before answering these questions, we would like to introduce the two model concepts of health care for birth(1).